2019
DOI: 10.5943/mycosphere/10/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, morphology and molecular phylogeny of Dothideomycetes on decaying wild seed pods and fruits

Abstract: Dothideomycetes is one of the largest and most diverse class of ascomycetes. Its members are reported from many plant parts, but less has been reported from wild seed pods and fruits. Dothideomycetes can be seed-borne or colonize fruits and seed pods when they fall to the ground. We studied the Dothideomycetes found on wild fruits and seed pods, mainly in Thailand (tropical), and to a lesser extent, in China (temperate) and UK (temperate). We describe eight new genera, 50 new species, provide 38 new host recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(201 citation statements)
references
References 45 publications
8
191
1
1
Order By: Relevance
“…Morphological structures were observed, and images captured using an optical microscope (Leica DM4500B, Leica microsystems GmbH, Wetzlar) equipped with a camera (Leica DFC320, Leica microsystems GmbH, Wetzlar). Macro-and microscopic features were compared with the available description of Roussoellaceae and Thyridariaceae [14,15,17,18,20].…”
Section: Morphological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological structures were observed, and images captured using an optical microscope (Leica DM4500B, Leica microsystems GmbH, Wetzlar) equipped with a camera (Leica DFC320, Leica microsystems GmbH, Wetzlar). Macro-and microscopic features were compared with the available description of Roussoellaceae and Thyridariaceae [14,15,17,18,20].…”
Section: Morphological Analysismentioning
confidence: 99%
“…A dataset consisting of nrSSU, nrITS, nrLSU, TEF1α and RPB2 was assembled on the basis of BLASTn results and of recent phylogenetic studies focused on Roussoellaceae and Thyridariaceae [18,20]. Reference sequences were retrieved from GenBank (Table 1).…”
Section: Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [54] reported 246 species in 116 genera from two unnamed Karst cave in Guizhou, China, including 20 new species. This first study is followed by a second [57,58]. In fact, the fungi on most terrestrial hosts in Asia have barely been studied and we predict that tens of thousands of species await discovery.…”
Section: Terrestrial Saprobesmentioning
confidence: 99%
“…typhicola forming only asexual state on the natural substrate (Hyde et al 2016) and Ps. bauhiniae producing both asexual and sexual states on the natural substrate (Jayasiri et al 2019). While the fungus found on the pseudothecia of Pa. polylepidis lacks a sexual state and forms uniloculate to multi-loculate pycnidia and pale brown, broadly ellipsoidal conidia, the species of Pseudocoleophoma usually produce a sexual state and pycnidia of the asexual state are uniloculate and the cylindrical conidia are hyaline.…”
Section: Taxonomymentioning
confidence: 99%